Comparators, study duration, outcome measures and sponsorship in therapeutic trials of psoriasis: update of the EDEN psoriasis survey 2001-2006 - Naldi, Luigi; Svensson, A.; Zenoni, D.; Diepgen, Thomas L.; Elsner, P.; Grob, J.-J.; Coenraads, P.-J.; Bouwes Bavinck, J.n.; Maccagni, A.; Linder, D.; Williams, H.; Network (EDEN), on behalf of the European Dermato-Epidemiology (British journal of dermatology, 2010)
Background Several new therapeutic options for psoriasis have been tested in clinical trials in recent years. Choice of comparator, study duration and outcome measures are critical for interpreting application of trial results to clinical practice. Objectives We examined whether these trial aspects have changed substantially in recent years in comparison with the past. Methods A systematic search and evaluation of all randomized controlled trials (RCTs) for psoriasis published from January 2001 up to December 2006 in 14 leading medical and dermatological journals, compared with those published from 1977 to 2000. Results There were 140 RCTs of psoriasis in the period 2001-2006 and 249 in the period 1977-2000. The proportion of placebo-controlled studies increased from 44·6% to 69·3%. The median study duration increased from 7 weeks to 12 weeks. The proportion of studies adopting the Psoriasis Area and Severity Index score as an outcome increased from 30·6% to 57·7%, while the number of studies incorporating a quality of life measure increased from only one (0·4%) to 12 studies (7·7%). The proportion of studies sponsored by pharmaceutical companies increased from 61·0% to 73·7%. Conclusions Despite the increased number of new options, the number of head-to-head comparative trials has decreased and most trials focus on short-term effects, probably reflecting the increased influence of industrial sponsorship on the research agenda.